THE IMPACT OF GROUP THERAPY ON SOCIAL RECOVERY IN DEPRESSION AND ANXIETY DISORDERS - Михайличенко, Марія (SWorldJournal, 2025)
The article explores the impact of group therapy on the social recovery of patients with depression and anxiety disorders. The aim of the study is to demonstrate how group therapy facilitates social rehabilitation and improves social functioning in the co